(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Dyslipidemia is major problem among population those have sedentary life style as well as in diabetics. Bougainvillea spectabilis is most commonly found in India as an ornamental plant and has got anti-diabetic action due to presence of one insulin mimicking agent D-pinitol (3-O-methyl-chiroinositol). The present investigation was undertaken to evaluate the effect of alcoholic extract of leaves of Bougainvillea spectabilis (AEBSL) on serum lipid profile in albino rats fed with high fat diet (HFD) and to compare it with a standard hypolipidaemic drug simvastatin. Thirty healthy albino rats of both sexes (100-200 g) were randomized into 5 groups of 6 animals each. The groups were treated as follows: Group A: normal diet (ND); Group B: HFD (vanaspati ghee + coconut oil mixture in ratio of 3:2 at 10 ml/kg/day); Group C: HFD+ AEBSL (100 mg/kg/day); Group D: HFD + AEBSL (200 mg/kg/day); Group E: HFD + simvastatin (1.8 mg/kg/day). Lipid profile was estimated after 8 weeks of treatment. AEBSL showed a significant (p<0.01) reduction in total cholesterol (TC), Triglyceride (TG), Low density lipoprotein (LDL), Very low density lipoprotein (VLDL) levels and significant (p<0.01) increase in high density lipoproteins (HDL) in hypercholesteromic rats (Group C and Group D). AEBSL 200 mg/kg/day found to be more effective than AEBSL 100 mg/kg/day. There is also significant improvement in atherogenic index (p<0.01) and increases the percentage of protection AEBSL treated animals. Alcoholic extract of leaves of Bougainvillea spectabilis leaves have excellent lipid lowering potentiality.